Metabotropic Glutamate Receptors Inhibit Microglial Glutamate Release - Stephen M McMullan; Bounleut Phanavanh; Gary Guo Li; Steven W Barger (ASN Neuro, 2012)
Pro-inflammatory stimuli evoke an export of glutamate from microglia that is sufficient to contribute to excitotoxicity in neighbouring neurons. Since microglia also express various glutamate receptors themselves, we were interested in the potential feedback of glutamate on this system. Several agonists of mGluRs (metabotropic glutamate receptors) were applied to primary rat microglia, and the export of glutamate into their culture medium was evoked by LPS (lipopolysaccharide). Agonists of group-II and -III mGluR ACPD [(1 S ,3 R )-1-aminocyclopentane-1,3-dicarboxylic acid] and L-AP4 [L-(+)-2-amino-4-phosphonobutyric acid] were both capable of completely blocking the glutamate export without interfering with the production of NO (nitric oxide); the group-I agonist tADA ( trans -azetidine-2,4-dicarboxylic acid) was ineffective. Consistent with the possibility of feedback, inhibition of mGluR by MSPG [( R,S )-α-2-methyl-4sulfonophenylglycine] potentiated glutamate export. As the group-II and -III mGluR are coupled to Gα i -containing G-proteins and the inhibition of adenylate cyclase, we explored the role of cAMP in this effect. Inhibition of cAMP-dependent protein kinase [also known as protein kinase A (PKA)] by H89 mimicked the effect of ACPD, and the mGluR agonist had its actions reversed by artificially sustaining cAMP through the PDE (phosphodiesterase) inhibitor IBMX (isobutylmethylxanthine) or the cAMP mimetic dbcAMP (dibutyryl cAMP). These data indicate that mGluR activation attenuates a potentially neurotoxic export of glutamate from activated microglia and implicate cAMP as a contributor to this aspect of microglial action.